Attenuation of cyclosporine A-induced testicular and spermatozoal damages associated with oxidative stress by ellagic acid - Türk, G; Sönmez, M; Çeribaşı, Ao; Yüce, A; Ateşşahin, A (My University, 2010)
This study was conducted to investigate the possible protective effect of ellagic acid (EA) on cyclosporine A (CsA)-induced testicular and spermatozoal damages associated with oxidative stress in male rats. Forty adult male Sprague–Dawley rats were divided into 4 groups of 10 animals each. Control group was used as placebo. Cyclosporine group received CsA at the dose of 15 mg/kg/day. Ellagic acid group was treated with EA (10 mg/kg/day). Cyclosporine plus ellagic acid group received CsA+EA. Reproductive organs were weighed and epididymal sperm characteristics and histopathological structure of testes were examined along with malondialdehyde (MDA) and glutathione (GSH) levels, glutathione-peroxidase (GSH-Px) and catalase (CAT) activities in testicular tissue. CsA significantly decreased the weights of testes and ventral prostate, epididymal sperm concentration, motility, testicular tissue glutathione (GSH), glutathioneperoxidase (GSH-Px) and catalase (CAT), diameters of seminiferous tubules and germinal cell layer thickness, and it significantly increased malondialdehyde (MDA) level and abnormal sperm rates along with degeneration, necrosis, immature germ cells, congestion and atrophy in testicular tissue. However, the CsA plus EA treatment attenuated all the CsA-induced negative changes observed in the testicular tissue, sperm and oxidant/antioxidant parameters. In conclusion, CsA-induced oxidative stress leads to the structural and functional damages in the testicular tissue and sperm quality of rats, and also EA has a protective effect on these damages.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Cyclosporine A Ellagic acid Lipid peroxidation Reproductive organs Sperm